DIRECTING PROBLEMS OF THE STATE DRAMA THEATER OF UZBEKISTAN - Israilova Mohina Adhamovna (Scholar Express Journal, 2024)
In this article, enlightened moderns, who understood that it is impossible to form the spirituality of the people, enrich the Islamic spirituality with new knowledge, and in the historical process, they made their proper contribution to the formation of the spirituality of people's faith and worldview. if there is, it is said that they sacrificed their lives.
Keywords: Science; Knowledge; Spirituality